The Role of Service and Product Quality on Customer Loyalty - Agus Taufik; Sugeng Santoso; Muhamad Irfan Fahmi; Faqih Restuanto; Steven Yamin (Journal of Consumer Sciences, 2022)
Coffee shops are today's businesses with good and competitive prospects in providing customer satisfaction and building customer loyalty. This study aims to analyze the relationship between service quality and product quality on customer satisfaction and loyalty, the relationship between customer satisfaction and customer loyalty, and the relationship between product and service quality and customer loyalty mediated by customer satisfaction. The study was conducted using quantitative methods, sampling a questionnaire to 100 customers of Coffee Shop. The study was conducted in August 2021. Meanwhile, to analyze the relationship between variables, using partial least squares (PLS). Based on the study results, it can be concluded that service quality directly affects customers, especially customer satisfaction. Product quality also affects customer satisfaction and loyalty and vice versa. However, service quality did not directly affect customer loyalty. Meanwhile, mediation through customer satisfaction and product quality indirectly affects customer loyalty.